Quantification of pectin-releasing activity of protopectinase-SE from Geotrichum klebahnii - Cavalitto, Sebastián Fernando (1997)
A method for quantification of a pectin releasing enzyme (PPase-SE) from Geotrichum klebahnii (= Geotrichum penicillatum = Trichosporon penicillatum) ATCC 42397 is reported. PPase activity was determined by measuring the amount of soluble pectin released from lemon protopectin. Particle size of the substrate, reaction time and linearity range of the assay, were analysed. The best assay conditions were a reaction time of 30 min, 20 mg substrate (mesh 60) and up to 0.045 units PPase activity per test tube.